The Effect of Etnographic-Based Outdoor Learning Methods on Learning Activities Class V Elementary School in Social Sciences - M Gita Primaniarta; Waspodo Tjipto Subroto; M Jacky (Studies in Philosophy of Science and Education, 2023)
he ethnographic-based Outdoor learning method is a learning method that conducts learning outside the classroom with a cultural approach in an area. The purpose of this study was to determine the effect of the Outdoor learning method on the activities of fifth grade students. The type of experimental method used is True-experimental through the Posttest Only Control Group Design procedure. The population used was class V at SDN Sidotopo Wetan IV and SDN Sidotopo Wetan V. Trials of questionnaire validation tests for 32 respondents with the provisions of tcount>ttable decided that 10 questionnaire were validated and reliable. The class prerequisite test uses the year-end assessment value using the homogeneity test through SPSS 25 with a value of 0.105>0.005 so that it is homogeneous. Testing the hypothesis through the T-test on the analysis of learning activities using numbers obtained a value of 0.002<0.05 so that Ha decision was accepted. . Based on the results of the study, it can be interpreted that the Ethnographic-Based Outdoor learning method has a positive and significant effect on the activities learning of fifth grade students.